2015
DOI: 10.1590/1807-3107bor-2015.vol29.0122
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatigue resistance of two nickel-titanium instruments in different curving angles: a comparative study

Abstract: The cyclic resistance of ProTaper Universal (size 25/08) and ProTaper Next (size 25/06) instruments was compared in artificial canals with different curvatures in this study. A total of 30 ProTaper Universal and 30 ProTaper Next instruments were divided into 6 groups (n = 10) and were operated into artificial canals with 3 different angles of curvature (45°, 60°, 90°). The canal length was kept consistent in this study. The number of cycles to fracture (NCF) was counted until file fracture occurred, at which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
4
11
0
2
Order By: Relevance
“…Similar results were shown in the study conducted by Cheng Peng et al , ProTaper NEXT files tended to be more resistant when operated in 45°and 60° canals, Considering that the majority of root canals are closer to being 45°or 60° artificial canals. 10 Another study conducted by Huseyin Sinan et al revealed that PTN X2 instruments exhibited greater cyclic fatigue resistance in the apical curvature of an artificial canal with a double curvature 11 ,which is in accordance with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were shown in the study conducted by Cheng Peng et al , ProTaper NEXT files tended to be more resistant when operated in 45°and 60° canals, Considering that the majority of root canals are closer to being 45°or 60° artificial canals. 10 Another study conducted by Huseyin Sinan et al revealed that PTN X2 instruments exhibited greater cyclic fatigue resistance in the apical curvature of an artificial canal with a double curvature 11 ,which is in accordance with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have demonstrated a change in the surface of rotary instruments after use ( 8 ). Although many previous studies have investigated various aspects of the ProTaper Next™ and ProTaper® Universal files, which include canal shaping ability ( 9 ), cyclic fatigue resistance ( 10 ), amount of debris extruded ( 11 ) etc., no studies have investigated how the surface and the alloy features would affect instrument fracture. Hence, the aim of this study was to analyze surface irregularities of these two rotary files before use and after instrumentation in curved canals in extracted human teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study are correlated with the results of the study conducted by Mohamed et al [25] who compared the cyclic fatigue resistance of five different NiTi rotary instruments. In the study by Peng et al [15], the fragment length of ProTaper Next instruments was significantly smaller compared to ProTaper Universal when they were examined in the canal at an angle of 90 degrees. However, there was no statistically significant difference in the length of fractured fragments in canals at an angle of 45 and 60 degrees.…”
Section: Discussionmentioning
confidence: 92%
“…The instruments are expected to be flexible and have a high cutting efficiency, which would ensure preservation of the initial form of the canal. However, sudden fracture of instruments inside the root canal is a major concern in daily clinical practice [15]. Cyclic fatigue is the main reason of instrument fracture occurring at the point of maximum instrument flexure while rotating within curved root canals [16].…”
Section: Discussionmentioning
confidence: 99%